Intelligenza artificiale e ortofoto per il censimento e la gestione delle aree pascolabili in ambiente alpino - Bovolo, Francesca (GEOmedia, 2021)
Mountain areas include precious environments like pastures that require preservation strategies by the appointed authorities. Here we present a system that processes orthophotos acquired by Agenzia per le Erogazioni in Agricoltura using Artificial Intelligence to reduce the time and costs of human inspection in pasture management activities. The system is trained to automatically classify multiple kinds of pasture and no-pasture areas. A user interface allows to query and refine the pasture maps. The map can be updated as new orthophotos come in. The system achieves good performance in the Provincia Autonoma di Trento (PAT), but it is suitable for similar mountain areas as well.